2007
DOI: 10.1016/j.cell.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

miR-181a Is an Intrinsic Modulator of T Cell Sensitivity and Selection

Abstract: T cell sensitivity to antigen is intrinsically regulated during maturation to ensure proper development of immunity and tolerance, but how this is accomplished remains elusive. Here we show that increasing miR-181a expression in mature T cells augments the sensitivity to peptide antigens, while inhibiting miR-181a expression in the immature T cells reduces sensitivity and impairs both positive and negative selection. Moreover, quantitative regulation of T cell sensitivity by miR-181a enables mature T cells to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
1,009
6
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,068 publications
(1,063 citation statements)
references
References 44 publications
(57 reference statements)
41
1,009
6
7
Order By: Relevance
“…For example, previous studies showed that miR‐181a regulates local immune balance (Liu et al ., 2012) and T‐cell sensitivity (Li et al ., 2007), although its mechanistic action remains unclear. We found that miR‐181a‐3p was coexpressed with and predicted to target three immune response genes, namely CXCL16 , RAB27A, and SPON2 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies showed that miR‐181a regulates local immune balance (Liu et al ., 2012) and T‐cell sensitivity (Li et al ., 2007), although its mechanistic action remains unclear. We found that miR‐181a‐3p was coexpressed with and predicted to target three immune response genes, namely CXCL16 , RAB27A, and SPON2 .…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression of miR-181a in mature T cells leads to a higher affinity for peptide antigens, whereas decreased expression of this miR in immature T cells results in a lower sensitivity and loss of negative and positive selection. Therefore, it seems that miR-181 works as an inherent antigen-sensitivity "rheostat" during the process of T cell development (Li et al 2007). Recently, it was found that miR-181d augmented the depletion of the DP thymocytes following LPS-induced stress, and a genetic study revealed that miR-181d can target a large number of metabolic as well as stress-signaling pathways and might play role in stress-induced ATI (Belkaya and van Oers 2014).…”
Section: Role Of Microrna During Bacterial Lps Stress-induced Atimentioning
confidence: 99%
“…In addition, miRNA have been found to control hematopoiesis (10), metabolism (11), and cardiac hypertrophy (12). It has been found that miRNA modulate T cell selection and T cell receptor sensitivity (13) as well as Treg cell development (14), which may suggest that miRNA are also involved in the development of autoimmunity. Recently, altered levels of miRNA have been linked to chronic inflammatory skin diseases (15).…”
mentioning
confidence: 99%